2004
DOI: 10.2118/86522-pa
|View full text |Cite
|
Sign up to set email alerts
|

Hot Oil and Gas Wells Can Be Stimulated Without Acids

Abstract: Summary A revolutionary family of treating fluids designed for the stimulation of critical, hot, or exotic oil and gas wells has been developed through application of detailed chemical and engineering studies.1-3 Formulations based on the hydroxethylaminocarboxylic acid (HACA) family of chelating agents have now been used to successfully increase production of oil and gas from wells in a variety of different formations. Included in the field test matrixes were new and producing wells drilled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…Chelating agents such as HEDAT and GLDA has low reaction rate by nature [20,21], GLDA has a unique property o f the low reaction rate with calcite which allows the use of GLDA at very low injection rates w ithout the fear of face dissolution. At high temperatures GLDA had a higher reaction rate compared to that at room temperature.…”
Section: Using Chelating Agents To Stimulate Shallow and Deep Carbonamentioning
confidence: 99%
“…Chelating agents such as HEDAT and GLDA has low reaction rate by nature [20,21], GLDA has a unique property o f the low reaction rate with calcite which allows the use of GLDA at very low injection rates w ithout the fear of face dissolution. At high temperatures GLDA had a higher reaction rate compared to that at room temperature.…”
Section: Using Chelating Agents To Stimulate Shallow and Deep Carbonamentioning
confidence: 99%
“…All of the three chemicals used formed wormholes in the tested cores. Frenier et al (2003 and2004) used formulations based on the hydroxy ethylaminocarboxylic acid (HACA) family of chelating agents to stimulate high temperature oil and gas carbonate reservoirs. Their laboratory tests showed that HACA chelating agents effectively stimulated carbonate formations at high temperatures (250 o F).…”
Section: Alternative Stimulation Fluids For Carbonate Formationsmentioning
confidence: 99%
“…If the reservoir pressure was not high, the damage may be permanent, as the precipitates may never be produced back. Frenier et al (2004) showed that HEDTA removed the calcium, magnesium, and iron carbonate minerals without inducing damage through clay degradation and precipitated byproducts in sandstone cores. Chelating agents were able to stimulate high temperature sandstone formations in the field; they removed the scale and stimulate the high-temperature wells.…”
Section: Chelating Agents In Sandstone Stimulationmentioning
confidence: 99%